Immunoconjugates as an Efficient Platform for Drug Delivery: A Resurgence of Natural Products in Targeted Antitumor Therapy - Rositsa Mihaylova; Denitsa Momekova; Viktoria Elincheva; Georgi Momekov (Pharmaceuticals)
The present review provides a detailed and comprehensive discussion on antibody–drug conjugates (ADCs) as an evolving new modality in the current therapeutic landscape of malignant diseases. The principle concepts of targeted delivery of highly toxic agents forsaken as stand-alone drugs are examined in detail, along with the biochemical and technological tools for their successful implementation. An extensive analysis of ADCs’ major components is conducted in parallel with their function and impact on the stability, efficacy, safety, and resistance profiles of the immunoconjugates. The scope of the article covers the major classes of currently validated natural compounds used as payloads, with an emphasis on their structural and mechanistic features, natural origin, and distribution. Future perspectives in ADCs’ design are thoroughly explored, addressing their inherent or emerging challenges and limitations. The survey also provides a comprehensive overview of the molecular rationale for active tumor targeting of ADC-based platforms, exploring the cellular biology and clinical relevance of validated tumor markers used as a “homing” mechanism in both hematological and solid tumor malignancies.